La Kriegsfibel di Bertolt Brecht, una teoria negativa - Fragapane, Giacomo Daniele (Rivista di studi di fotografia. Journal of Studies in Photography, 2015)
Published in 1955, after many problems due to its radical, ideological position, today Bertolt Brecht’s Kriegsfibel may be described as a ‘negative theory’ of photography. In its utopian and antimodernist structure we can detect several crucial themes of the modern reflection on what is “photographic” and a radical critique of the notion of the “author”. Brecht’s method goes against contemporary photographic historiography that institutionalizes a “classic”, dominant mode of production, and the idea of the medium’s specificity.